Determination of Aflatoxin B(1) in Smokeless Tobacco Products by use of UHPLC-MS/MS - Zitomer, Nicholas (J Agric Food Chem, 2015)
We have developed a UHPLC-MS/MS method for the detection and quantitation of aflatoxins in smokeless tobacco products and used it to determine aflatoxin B(1) concentrations in 32 smokeless tobacco products commercially available in the US. Smokeless tobacco products were dried, milled and amended with (13)C(17)-labelled internal standards, extracted in water/methanol solution in the presence of a surfactant, isolated through use of immunoaffinity column chromatography and reconstituted in mobile phase prior to UHPLC-MS/MS analysis. Our method was capable of baseline separation of aflatoxins B(1), B(2), G(1) and G(2) in a 2.5 min run by use of a fused core C(18) column and a water/methanol gradient. MS/MS transition (m/z) 313.3>241.2 was used for aflatoxin B(1) quantitation, with 313.3>285.1 used for confirmation. The limit of detection (LOD) for aflatoxin B(1) was 0.007 parts per billion (ppb). Method imprecision for aflatoxin B(1) (expressed as coefficient of variation) ranged from 5.5% to 9.4%. Spike recoveries were 105–111%. Aflatoxin B(1) concentrations in the smokeless tobacco products analysed ranged from <LOD to 0.271 ppb (dry mass). Aflatoxin B(1) was most frequently detected in dry snuffs and chews, whereas all moist snuff products tested were below LOD. The amounts of aflatoxin B(1) we detected were low relative to the 20 ppb regulatory limit established by the Food and Drug Administration for foods and feeds.